Perancangan Perbaikan Bisnis Proses Dan Perancangan Perangkat Lunak Sistem Pengolahan Koran Pada PT. Madura Mandiri Indonesia Sejahtera Menggunakan The Open Group Architecture Framework (ADM) - Moch. Rosul Zein; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Madura Mandiri Indonesia Sejahtera is a print media company called Kabar Madura. From the business processes, there are several potential problems that interfere the processing of newspapers, which is the number of bureaucracy that causes delays in the distribution of goods. So far the company doesn't have an integrated system in processing all business activities, recording and processing company information flow that is prone to errors because it is still done manually, the flow of information is related to data processing news, ad registration, ad extension, design & layouting, and also data related to the processes that exist in the company. Based on these problems, it is necessary to design enterprise architecture to conduct analysis, evaluation and information systems. This study uses the TOGAF Architectur Development Method (ADM), Business Process Modeling Notation (BPMN) is used to identify needs, Business Process Improvement (BPI) to determine the improvement, in the design and implementation using the OOP technique approach and software functionality testing using the blackbox method. From the results of simulations carried out by the business process (As Is) and business processes (To Be) on advertising registration, an increase in Time Analysis reached 47.1%. The results of functionality testing that has been done indicate that this system has met the needs in accordance with the specified specifications. By doing black box testing it has 17 test cases, and the test results are stated to be 100% successful.